(untitled) (Semiárida, 2020)
The evaluation of inbred lines within a program of hybrid maize requires not only the determination of lines production per-se but also that of the average behaviour of their hybrid combinations (General Combining Aptitude) and their capacity to produce higher hybrid combinations among them (Specific Combining Aptitude). The aim of this work was the analysis of the General Combining Aptitude (GCA) of eleven forage maize inbred lines derived from the original crossing between Zea mays L. x Zea diploperennis Iitis, Doebley and Guzman, and the Specific Combining Aptitude (SCA) of the progeny of a pimple and direct diallelic among them. The total aerial plant forage mass and their morphological components are evaluated in comparison with a commercial hybrid. The GCA/SCA rate was high for all the production characters evaluated, showing low dominance effect or over-dominance, maybe due to a slight difference among lines. GCA was found to be significant for the production of leaves -line 4 (LE 785) presented the highest values and was also favoured with the GCA highest values for stem and whole plant. Line 2 (LE 769) GCA was found satisfactory for corncob production. The crossing (2 x 4) showed good behaviour in the production of forage and since this is due to the genetic contribution of their progeny lines, it would be interesting to begin a recurrent selection program, starting with the first segregating generation of this crossing, trying a favourable gene recombination of the forage mass.